From high oleic vegetable oils to hydrophobic starch derivatives: II. Physicochemical, processing and environmental properties. (1st September 2020) - Zarski, Arkadiusz; Bajer, Krzysztof; Raszkowska-Kaczor, Aneta; Rogacz, Diana; Zarska, Sandra; Kapusniak, Janusz
Highlights: Films of medium substituted starch esters were successfully produced by extrusion. Films exhibited increased hydrophobicity and improved mechanical properties. Starch ester films retained their biodegradability and non-phytotoxicity. Abstract: Medium-substituted esters of starch and higher fatty acids, structurally identified in the first part of paper were subjected to further analyses, mainly to check application potential. In order to determine the possibility of using the esters in the packaging industry, the glycerol-plasticized starch esters were extruded on a single screw extruder in the form of a film. The mechanical properties tests consisted of tensile and tear strength. Hydrophobicity, water absorption and oil absorption were checked as the processing and functional properties. Environmental tests, such as phytotoxicity on monocotyledonous and dicotyledonous plants and biodegradability in soil under strictly controlled conditions of the vegetation hall were carried out. Esterification increased the hydrophobicity of the starch and the tensile and tear strength, without losing important environmental features such as biodegradability and non-toxicity. The obtained polymer materials give hope for their use in the production of new ecofriendly and biodegradable packaging.